2019
DOI: 10.1016/j.psychres.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depressive symptoms on executive functioning in binge eating disorder: A comparison of patients and non-obese healthy controls

Abstract: Executive functions are a set of cognitive processes that are necessary for the cognitive control of behavior. They play a role in mediating self-control, self-regulation and decision-making. It has been suggested that the inability to control eating behavior in binge eating disorder (BED) may indicate deficits in executive functioning. This may be worsened by depressive symptoms. The aim of the present study was to compare executive functioning of patients with BED and no-to-mild depressive symptoms (n = 25),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 55 publications
2
28
1
Order By: Relevance
“…Qualitative inspection of the literature indicated mixed, inconclusive findings for control inhibition, decision making and cognitive flexibility in individuals with BED compared to controls (obese or normal weight), we will discuss it later. Only one small metaanalysis (n = three studies, 200 participants in total) suggested poorer working memory performance in people with BED compared to obese individuals without BED (29,30,33), with a small effect size.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Qualitative inspection of the literature indicated mixed, inconclusive findings for control inhibition, decision making and cognitive flexibility in individuals with BED compared to controls (obese or normal weight), we will discuss it later. Only one small metaanalysis (n = three studies, 200 participants in total) suggested poorer working memory performance in people with BED compared to obese individuals without BED (29,30,33), with a small effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Six additional studies not included in the meta-analysis reported mixed findings. In three studies, there was no evidence of altered performance in the BED group compared to obese (18,37,41) or normal weight controls (18,33). In one study (56), individuals with BED showed poorer performance compared to normal weight controls on all indexes of the WCST, apart from perseverative errors.…”
Section: Perseverative Errors: Wcst Pcet and Iedmentioning
confidence: 90%
See 3 more Smart Citations